SEMIOTIC ANALYSIS: MUSIC GENRES AND FASHION EXPRESSION AMONG ENGLISH LITERATURE STUDENTS AT UNIVERSITAS SUMATERA UTARA - Yulia Pradinda; Muhammad Fakhran al Ramadhan (Prodi Sastra Inggris UKI, 2024)
This study used Charles Sanders Peirce's semiotic theory to analyze the influence of music genre on the fashion expression of English Literature students at the University of North Sumatra. This research used a descriptive qualitative method. Data was obtained through structured interviews with three informants who have preferences in punk, alternative rock, and K-pop music genres. The results show that each music genre influences different fashion elements regarding colors, accessories, and clothing styles. The punk genre reflects the values of freedom and resistance through dark colors and distinctive accessories, alternative rock highlights self-expression through edgy fashion elements, while K-pop carries modernity and femininity with pastel colors and styles inspired by Korean popular culture. The environment of USU's Faculty of Humanities also plays a vital role in supporting the diversity of student fashion expressions to interact with music subcultures and social identities. Thus, fashion is not only a visual representation of musical preferences but also functions as a sign system that communicates the identity, values, and affiliations of the student community on campus.